2020
DOI: 10.1177/1362361320951696
|View full text |Cite
|
Sign up to set email alerts
|

‘I’m not just a guinea pig’: Academic and community perceptions of participatory autism research

Abstract: Despite calls for increased community engagement in autism research, the published evidence base suggests that participatory autism research remains rare. This study examined the extent and nature of community engagement in Australian research projects commissioned by the Autism CRC. Data were gathered using an online survey, comprising quantitative scale items and qualitative free-text responses, which was completed by 64 academic partners and 15 community partners. Quantitative findings indicated that autism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
65
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 50 publications
5
65
0
2
Order By: Relevance
“…This is especially important given the reported generalization (Carruthers et al, 2020;Ostmeyer & Scarpa, 2012;Rao et al, 2008) and maintenance (Bellini et al, 2007;Neely et al, 2016;Rogers, 2000) benefits of practice-based research. Thirdly, future research should consider seeking input from teachers, peers and also children with ASD, as reflected within broader participatory research recommendations (den Fletcher-Watson et al, 2019;Houting et al, 2020;Jivraj et al, 2014;Lau & Stille, 2014) and, consequently, add to the social validity of this evidence base. Fourthly, given that the vast majority of play-based interventions included in this review were based on predominately male samples across the UK and USA, future research may consider including more geographical and gender representative samples, as identified within other systematic reviews in the field (Gibson et al, 2020;Kossyvaki & Papoudi, 2016;Stiller & Mößle, 2018).…”
Section: Recommendations For Future Practice-based Research In the Field Of Autism Play And Social Communication Developmentmentioning
confidence: 99%
“…This is especially important given the reported generalization (Carruthers et al, 2020;Ostmeyer & Scarpa, 2012;Rao et al, 2008) and maintenance (Bellini et al, 2007;Neely et al, 2016;Rogers, 2000) benefits of practice-based research. Thirdly, future research should consider seeking input from teachers, peers and also children with ASD, as reflected within broader participatory research recommendations (den Fletcher-Watson et al, 2019;Houting et al, 2020;Jivraj et al, 2014;Lau & Stille, 2014) and, consequently, add to the social validity of this evidence base. Fourthly, given that the vast majority of play-based interventions included in this review were based on predominately male samples across the UK and USA, future research may consider including more geographical and gender representative samples, as identified within other systematic reviews in the field (Gibson et al, 2020;Kossyvaki & Papoudi, 2016;Stiller & Mößle, 2018).…”
Section: Recommendations For Future Practice-based Research In the Field Of Autism Play And Social Communication Developmentmentioning
confidence: 99%
“…Although the involvement of autistic community members in research teams is an important topic for the field, it has been discussed in other publications. [6][7][8][9][10][11] Furthermore, while the accessibility of university-based clinical programs (e.g., medical, education, social work, and clinical psychology) does affect the representation of autistic people in occupations that are responsible for providing important services and supports to autistic individuals, this is a distinct and separate topic from autism research. Finally, this roundtable does not explore experiences of autistic people conducting research in fields unrelated to autism.…”
Section: Introductionmentioning
confidence: 99%
“…
Recently, there has been a push to increase research engagement within the autism community. Historically, research engagement has largely focused on childhood disability research and participatory autism research remains rare (den Houting et al, 2021). This gap in the literature can often result in the substitution of parents' voices for those of their Autistic children within the framework of family-centred services.
…”
mentioning
confidence: 99%
“…Résumé Récemment, la communauté de l'autisme a exercé des pressions pour accroître sa participation à la recherche. Historiquement, l'engagement de la recherche s'est largement concentré sur le handicap infantile, et la recherche participative sur l'autisme reste rare (den Houting et al, 2021).Cette lacune dans la littérature scientifique peut souvent entraîner la substitution des voix des parents à celles de leurs enfants autistes dans le cadre des services centrés sur la famille. Cet article soutient que l'engagement dans la recherche devrait être mené de manière à représenter la communauté de l'autisme dans son ensemble.…”
unclassified
See 1 more Smart Citation